Isaac Kalimi, Writing and rewriting the story of Solomon in Ancient Israel. Cambridge, Cambridge University Press, 2018. 402 pp. ISBN-13: 978- 3447113632 (Hardback). USD 125.00 - Andiñach, Pablo R. (2020)
Fil: Andiñach, Pablo R. Pontificia Universidad Católica Argentina. Facultad de Ciencias Sociales; Argentina